Infinity ankle arthroplasty with traditional instrumentation and PSI prophecy system: preliminary results - Giardini, Piero; Di Benedetto, Paolo; Mercurio, Domenico; Gisonni, Renato; Molinari, Marco; Causero, Araldo; Cortese, Fabrizio (Acta Biomedica Atenei Parmensis, 2020)
Ankle arthrodesis has been considered the surgical Gold Standard for advanced ankle arthritis; prosthetic replacement of the tibio-talar joint played a secondary role.The introduction of last generation ankle prostheses lead to better outcome and a lower rate of complication. PSI represents the most recent innovations introduced on the market of ankle arthroplasty:PSI is proposed as a surgical technique capable of making ankle arthroplasty more accurate and more reproducible compared to standard referencing guides Aim of the study is to report early clinical and radiographic outcomes obtained from a single surgeon experience by implanting the same ankle prosthesis using a standard (STD) or a PSI instrumentation Unlike no difference in the average increment of normalized sub score related to function in each group (PSI vs STD), the analysis of normalized pain sub score pointed out a greater average improvement in the PSI group(+75%)compared to the STD group(+62%);this result has been adovacated to the absence of post operative gutter impingement syndrome in the PSI group compared to the STD referencing group. The analysis of radiographic angles revealed a more accurate and reproducible positioning of the components in the PSI group; ankle arthroplasty performed with PSI reported a reduction of both surgical times and the need of intraop.fluoroscopy. PSI ankle arthroplasty achived more accurate and reproducible clinical and radiographic results compared to STD instrumentation;long-term follow-up are needed to demonstrate whether a better positioning of the implant is associated with an increased survival of the prosthesis and therefore justifies the additional costs of PSI.